2018
DOI: 10.1038/s41387-017-0013-x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of pronounced changes in the expression of fatty acid handling proteins in adipose tissue and plasma of morbidly obese humans

Abstract: Background/ObjectivesFatty acid handling proteins are involved in the process of accumulation of lipids in different fat tissue depots. Thus, the aim of the study was to estimate the expression of both fatty acid transport and binding proteins in the subcutaneous (SAT) and visceral adipose tissue (VAT) of patients with morbid obesity without metabolic syndrome, as well as the plasma concentrations of these transporters.Subjects/MethodsProtein (Western blotting) and mRNA (Real-time PCR) expression of selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The data on FAT/CD36 in human adipose tissue are very sparse. A previous study demonstrated greater expression of FAT/CD36 in VAT in patients with obesity compared with lean patients . Fisher et al observed that the expression of FAT/CD36 was higher in patients with obesity.…”
Section: Discussionmentioning
confidence: 93%
“…The data on FAT/CD36 in human adipose tissue are very sparse. A previous study demonstrated greater expression of FAT/CD36 in VAT in patients with obesity compared with lean patients . Fisher et al observed that the expression of FAT/CD36 was higher in patients with obesity.…”
Section: Discussionmentioning
confidence: 93%
“…At the same time it was shown earlier that SAT and VAT FABP4 gene expression level did not differ between normally weighing and metabolically healthy obese individuals (Garin-Shkolnik et al, 2014;Grzegorczyk et al, 2018). However, contradictory results have been published with respect to FABP4 gene expression in patients with metabolic complications and diabetes.…”
Section: Discussionmentioning
confidence: 92%
“…In order to further characterise THCB as a potent PPARγ ligand, the effects of the compound on the expression levels of PPARγ target genes were determined in differentiated 3T3-L1 cells. The selected PPARγ target genes were lipoprotein lipase (LPL) which is involved in lipid metabolism [ 31 ] and adipocyte fatty acid binding protein (AP2) which is involved in uptake and metabolism of fatty acids as well as the modulation of specific enzymes of lipid metabolism, cell growth and differentiation [ 32 ], adiponectin which is closely associated with insulin sensitivity [ 33 ], and, fatty acid translocase (CD36), a type of membrane fatty acid handling proteins [ 34 ].These genes were also used by Jeong et al [ 35 ] to study the induction of PPARγ target genes by its ligands in 3T3-L1 adipocytes. In the gene expression experiment, THCB was used at 212 nM because this compound has shown the highest adipocyte differentiation activity at this concentration, as demonstrated in Figure 3 c.…”
Section: Resultsmentioning
confidence: 99%